KUALITAS AUDIT, PROFITABILITAS, STRUKTUR MODAL, PERTUMBUHAN PERUSAHAAN, DAN UKURAN PERUSAHAAN DALAM PENGARUHNYA TERHADAP NILAI PERUSAHAAN - Dianita Meirini; Novi Khoiriawati (Politeknik Keuangan Negara STAN, 2021)
The decline in the value of the market capitalization of manufacturing companies in 2020 worth 309 trillion indicates that the value of manufacturing companies has declined during the COVID-19 pandemic. This study aims to determine the factors that influence the decline in the value of manufacturing companies during the covid-19 pandemic. Factors suspected and tested in this study to influence the value of manufacturing companies during the covid-19 pandemic are audit quality, profitability, capital structure, firm growth, and firm size. This research is a quantitative study using data from manufacturing companies that are regularly listed on the Indonesian Stock Exchange and submit annual reports for 2018-2020. The sample used is made up of 12 manufacturing companies with reasoned sampling as the sampling method. The results of the study indicate that profitability and capital structure have a significant positive effect on the value of manufacturing firms during the covid-19 pandemic. While firm size has a significant negative effect on the value of manufacturing firms during the covid-19 pandemic and the quality of audits and firm growth have no effect on the value of manufacturing firms during the covid-19 pandemic.